The Development of the Sariswara Method in Accommodating the Students' Diversity in Thematic Learning Material of Elementary School - Andini, Dinar Westri; Hufad, Achmad; Rochyadi, Endang; Aprilia, Imas Diana; Annisa, Firyalina Yulma; Praheto, Biya Ebi; Taryatman, Taryatman (Asosiasi Dosen PGSD dan Dikdas Indonesia, 2023)
This research describes the Sariswara Method and syntax development in Accommodating Student Diversity. This research was conducted at Kemudo 3 Elementary School. It used observation, interviews, and questionnaires as data collection techniques. The research method used is Research and Development. The method developed used the 6 steps of Borg & Gall development by Sugiyono (1) research and collecting information, (2) data collection, (3) product design, (4) expert validation, (5) product revisions, (6) and limited trials. The results of this research and development method indicate that the Sariswara method and syntax have been successfully developed. The feasibility score is a